The Vpu protein of human immunodeficiency virus type 1 forms cation-selective ion channels. - Ewart, G D (1996)
Vpu is a small phosphorylated integral membrane protein encoded by the human immunodeficiency virus type 1 genome and found in the endoplasmic reticulum and Golgi membranes of infected cells. It has been linked to roles in virus particle budding and degradation of CD4 in the endoplasmic reticulum. However, the molecular mechanisms employed by Vpu in performance of these functions are unknown. Structural similarities between Vpu and the M2 protein of influenza A virus have raised the question of whether the two proteins are functionally analogous: M2 has been demonstrated to form cation-selective ion channels in phospholipid membranes. In this paper we provide evidence that Vpu, purified after expression in Escherichia coli, also forms ion channels in planar lipid bilayers. The channels are approximately five- to sixfold more permeable to sodium and potassium cations than to chloride or phosphate anions. A bacterial cross-feeding assay was used to demonstrate that Vpu can also form sodium-permeable channels in vivo in the E. coli plasma membrane.